Komparasi Fungsionalitas EVE-NG dan GNS3: Simulasi Protokol Jaringan - Sholeha, Eka Wahyu; Jaya, Dery Yuswanto; Supriyanto, Arif; Utomo, Hendrik Setyo (Universitas Islam Negeri Sumatera Utara, 2025)
The development of network technology drives the need for efficient, flexible, and economical simulation tools for learning and testing network architectures. This research compares two popular platforms, GNS3 (Graphical Network Simulator-3) and EVE-NG (Emulated Virtual Environment - Next Generation), in terms of functionality, network performance, and resource consumption. Testing was carried out through network protocol simulations with identical topologies, and parameters such as throughput, delay, jitter, packet loss, convergence time, and CPU, RAM, and disk I/O usage were measured. The results show that EVE-NG is more stable with high throughput, low jitter, and optimal transmission efficiency, making it suitable for complex simulations. Meanwhile, GNS3 is more resource-efficient and has faster convergence, ideal for basic learning. The conclusion of this research emphasizes that the choice of platform depends on the needs: EVE-NG for large scale, GNS3 for education. These findings provide guidance for educators, professionals, and researchers in choosing simulation tools according to the context. Keywords: Network Simulation, GNS3, EVE-NG, Protocol Emulation, Performance Evaluation